Pengaruh Latar Belakang Ekonomi Keluarga Terhadap Perilaku Siswa Kelas V SDN Semanggi Lor - Lukita Apsari; Muhammad Abduh (Educatio, 2025)
One indicator of family welfare can be observed through economic conditions, which play a crucial role in improving the standard of living. A stable family environment provides positive stimuli and responses that affect children's development, including their behavior. This study aim to research the economic situations of poor households affect the conduct of fifth-grade pupils at Semanggi Lor Elementary School. The research approach employed is quantitative using the sort of field study and an ex-post facto research design. The subjects of the study included all fifth-grade students who received the Smart Indonesia Program (PIP) at Semanggi Lor Elementary School, with a total of 40 students. Data was gathered using a Likert scale-based questionnaire. Data analysis approaches include deductive statistics. such as instrument testing (validity and reliability), prerequisite testing, and hypothesis testing. The results showed a constant value (a) = 131,700 and a regresion coeficient (X) = -0.918, so that the equation model Y = 131,700 + (-0.918) X was obtained. From this model, it can be concluded that the effect of variable X on Y is negative. The significance test produces a sig value greater than 0.05 (0.277 > 0.05), This signifies that Ha is rejected whereas Ho is approved. Thus, it is possible to conclude that family economic situations (X) have no substantial impact on the conduct of fifth-grade kids (Y) at Semanggi Lor Elementary School.